Thermoelectric effect in layered conductors in a strong magnetic field - Kirichenko, O.V.; Peschansky, V.G.; Galbova, O.; Ivanovski, G.; Krstovska, D. (Condensed Matter Physics, 2006)
We have theoretically studied the thermoelectric effect in layered conductors with a quasi-two-dimensional
electron energy spectrum of an arbitrary form in a quantizing magnetic field at low temperatures. Giant quantum
oscillations of thermoelectric field versus the inverse magnetic field have been predicted, which will facilitate
the experimental study of quantum oscillatory effects. Thermoelectric force in a layered conductor is
shown to depend periodically upon the angle between the magnetic field direction and the normal to the
layers. This orientation effect arises from the quasi-two-dimensional character of the charge carriers energy
spectrum and is representative of layered conductors Теоретично вивчено термоелектричнi та термомагнiтнi явища у шаруватих провiдниках з квазiдвовимiрним електронним енергетичним спектром довiльного виду в квантуючому магнiтному полi при
низьких температурах. Передбачено iснування гiгантських осциляцiй термоелектричного поля як
функцiї оберненої величини магнiтного поля, що полегшує експериментальне вивчення квантових
осциляцiйних явищ. Показано, що термоелектричнi коефiцiєнти шаруватого провiдника є перiодично залежними вiд кута мiж напрямком магнiтного поля та нормаллю до шарiв. Цей орiєнтацiйний
ефект пов’язаний з квазiдвовимiрнiстю енергетичного спектру носiїв заряду i є характерним для
шаруватих провiдникiв.